Silencing Marcellus: When the Law Fractures Public Health - Marks, Jonathan H. (The Hastings Center report, 2014)
We tend to think of conflict as bad and compromise as good. But how should we view conflict that exposes potential threats to the environment and health? And what about a compromise between litigants that may adversely affect the interests of third parties or undermine public health? There can be few places in the country where this issue has become more pressing than in my home state, Pennsylvania. The hydraulic fracturing of natural gas in the Marcellus Shale has transformed lives and landscapes here, mainly in rural communities with low-income populations. The Hallowich family is a case in point.